MENGUNGKAP SISI KECERDASAN DALAM PROSES PEMAHAMAN AKUNTANSI - Dewa Ayu Julia Oka; Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2021)
Emotional Quotient (EQ) determines how well a person uses her skills. Spiritual Quotient (SQ) is the foundation necessary for the functioning of Intellectual and Emotional quotient effectively. The informants in this study were 3 undergraduate students of Accounting Department, Faculty of Business and Tourism Economics, University of Hindu Indonesia. In this study, researchers used a qualitative approach. The research approach used was the Phenomenology of Edmund Hussel. The main objective of this research is to analyze and analyze the phenemoenology of accounting understanding from the point of view of emotional and spiritual intelligence. From the results of the research, these three informants have a weak understanding of accounting from the point of view of intelligence. This can be seen from the "in order to motive" of students in lectures only pursuing a high achievement index by justifying all means including cheating and using mobile phones with "because motiveâ€ the three informants who seen from the point of view of intelligence intelligence, namely the way lecturers teach courses and students tend to race on textbooks and mobile phones. Researchers found the results of the informant's "because motive", namely the informant is distant from religious values such as a lack of calm and rarely pray when answering assignments or exams.